The SGLT2 inhibitor checklist: a comprehensive review of perioperative and acute phase safety management - Deng, Bin; Liu, Wenhua; Chu, Qingmin (Frontiers in Endocrinology, 2026)
Sodium-glucose cotransporter-2 (SGLT2) inhibitors have transcended their initial designation as mere glucose-lowering agents to become a foundational pillar in the management of cardiorenal metabolic syndrome. Their cardiorenal benefits have made them ubiquitous in surgical patients, including those without diabetes. However, this therapeutic triumph has introduced a unique and deceptive perioperative challenge: euglycemic diabetic ketoacidosis (euDKA). This metabolic emergency, characterized by severe metabolic acidosis and ketosis in the absence of significant hyperglycemia, poses a diagnostic dilemma that continues to jeopardize patient safety. This comprehensive review synthesizes the rapidly evolving landscape of perioperative SGLT2 inhibitor management as of 2025. We provide an exhaustive dissection of the endocrine mechanisms driving ketogenesis, challenging the canonical “insulin-deficiency” model by integrating novel data on human pancreatic α-cell SGLT1 expression, renal sodium-monocarboxylate transporter (SMCT) upregulation, and the newly elucidated arginine vasopressin (AVP)-V1b receptor axis which mechanistically links dehydration to hyperglucagonemia. Furthermore, we critically adjudicate the conflicting clinical evidence emerging in 2024-2025, juxtaposing the reassuring “natural experiment” data from JAMA Surgery against the persistent safety signals in BMJ Open and anesthesia literature. We analyze the risks of “rebound” heart failure associated with medication withdrawal—citing specific hazard ratios for readmission—and provide a comparative analysis of divergent international guidelines (FDA, EMA, ANZCA, JBDS). Finally, we propose a physiologically grounded, risk-stratified clinical decision framework to guide the perioperative suspension and resumption of these potent agents.